Strontium isotope ratios related to childhood mobility: Revisiting sampling strategies of the calcined human pars petrosa ossis temporalis. (2nd February 2021) - Veselka, Barbara; Locher, Heiko; de Groot, John C.M.J.; Davies, Gareth R.; Snoeck, Christophe; Kootker, Lisette M.
Abstract : Rationale: Strontium isotope analysis can be applied to the calcined human otic capsule in the petrous part (pars petrosa ossis temporalis; PP) to gain information on childhood mobility in archaeological and forensic contexts. However, only a thin layer of the otic capsule, the inner cortex, demonstrates virtually no remodelling. This paper proposes an improved sampling method for the accurate sampling of the inner cortex of the otic capsule to ensure that 87 Sr/ 86 Sr ratios related to early childhood are obtained. Methods: Calcined rib and diaphyseal fragments and PP from ten cremation deposits are sampled for strontium isotope analysis, whereby our improved sampling strategy is applied to sample the inner cortex of the otic capsule. This allows inter‐ and intraskeletal 87 Sr/ 86 Sr comparison within an Iron Age collection from Oss, The Netherlands. Results: Forty percent (4/10) of the calcined PP that were evaluated for this study show marked differences in 87 Sr/ 86 Sr (0.00035–0.00065) between the inner cortex and the bone sample surrounding this layer, the external cortex that has higher remodelling rates. Differences in 87 Sr/ 86 Sr between various skeletal elements also aided in the identification of the minimum number of individuals. Conclusions: Our study demonstrates the problematic nature of the external cortex and stresses the need for a precise sampling method of the correct areas of the otic capsule. This can only be obtained by cutting the calcined PP midmodiolarly to enable adequate combustion degree assessment, and the correct identification and sampling of the inner cortex of the otic capsule.